2016
DOI: 10.1038/cdd.2016.61
|View full text |Cite
|
Sign up to set email alerts
|

The apoptotic members CD95, BclxL, and Bcl-2 cooperate to promote cell migration by inducing Ca2+ flux from the endoplasmic reticulum to mitochondria

Abstract: Metalloprotease-processed CD95L (cl-CD95L) is a soluble cytokine that implements a PI3K/Ca2+ signaling pathway in triple-negative breast cancer (TNBC) cells. Accordingly, high levels of cl-CD95L in TNBC women correlate with poor prognosis, and administration of this ligand in an orthotopic xenograft mouse model accelerates the metastatic dissemination of TNBC cells. The molecular mechanism underlying CD95-mediated cell migration remains unknown. Here, we present genetic and pharmacologic evidence that the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…Antiapoptotic Bcl-XL and MCL1 both bind to VDAC1 and VDAC3 isoforms to promote mitochondrial Ca 2+ uptake and drive cell migration ( 77 80 ). Importantly, disrupting the Bcl-XL-VDAC and MCL1-VDAC interactions was found to inhibit migration of triple negative breast cancer cells ( 80 ) and non-small cell lung carcinoma cells, respectively ( 78 ). These data raise the possibility of suppressing invasion and metastasis by targeting VDAC-Bcl-2 protein interactions.…”
Section: Involvement Of Er-mitochondrial Ca 2+ Flumentioning
confidence: 99%
“…Antiapoptotic Bcl-XL and MCL1 both bind to VDAC1 and VDAC3 isoforms to promote mitochondrial Ca 2+ uptake and drive cell migration ( 77 80 ). Importantly, disrupting the Bcl-XL-VDAC and MCL1-VDAC interactions was found to inhibit migration of triple negative breast cancer cells ( 80 ) and non-small cell lung carcinoma cells, respectively ( 78 ). These data raise the possibility of suppressing invasion and metastasis by targeting VDAC-Bcl-2 protein interactions.…”
Section: Involvement Of Er-mitochondrial Ca 2+ Flumentioning
confidence: 99%
“…In fact, 2 studies carried out in patients with systemic scleroderma showed that blood drawn 1 day after ECP had a high frequency of CD4 T cells with a high expression of CD95, a major regulator of extrinsic apoptosis [31, 32]. In vitro studies suggest that CD95 can cooperate with Bcl-xL and Bcl-2 to mobilize Ca2+ inside the mitochondria [33]. In mouse epidermal cells, exposure to 8-MOP/UVA results in p53 stabilization and nuclear translocation that triggers CD95 expression as early as 48 h after irradiation [34, 35].…”
Section: Mitochondrial Alterations and Bcl-2 Family Proteinsmentioning
confidence: 99%
“…Other proteins localized to MAMs are VDAC and IP3R, the action of which is dependent on Bcl-2 family proteins and, in addition to their role in apoptosis, partly regulate Ca 2+ signaling via their complex with MAM proteins (Monaco et al, 2015;Bittremieux et al, 2019). Anti-apoptotic family members Bcl-2, Bcl-XL, and Mcl-1 bind to VDACs and suppress mitochondrial Ca 2+ transport that in turn supports cell migration and invasion (Huang et al, 2013(Huang et al, , 2014Fouqué et al, 2016). Both Bcl-2 and Bcl-XL interact with VDAC1 through BH4 domain; however, Bcl-XL BH4 is more effective than Bcl-2-BH4 in targeting VDAC1 activity (Monaco et al, 2015).…”
Section: Er-mitochondria Network and Metastasismentioning
confidence: 99%
“…Both Bcl-2 and Bcl-XL interact with VDAC1 through BH4 domain; however, Bcl-XL BH4 is more effective than Bcl-2-BH4 in targeting VDAC1 activity (Monaco et al, 2015). Dissociation between these anti-apoptotic Bcl-2 family members and VDACs results in decreased migration of TNBC (Fouqué et al, 2016) and NSCLC cells (Huang et al, 2014). Bcl-2 family proteins could also interact with IP3R suppressing Ca 2+ -release.…”
Section: Er-mitochondria Network and Metastasismentioning
confidence: 99%